Fabrication of controllable and reversible bidirectional shape memory fabric composites based on multiblock copolyimide and their properties. (16th January 2023) - Zhou, Xinyan; Zhao, Xin; Li, Xiuting; Dong, Jie; Xu, Weilin; Zhang, Qinghua
Abstract: The construction of polymer-based materials with reversible bidirectional shape memory effects and good thermal properties is of paramount importance for the development of the intelligent exploration in high temperature fields. In this work, a series of multiblock shape memory copolyimides were synthesized with the introduction of soft segments containing aliphatic diamines into aromatic polyimide structures to control the mobility of the molecular chains. The number of blocks for copolyimide was finely regulated to optimize the shape memory behaviors with thermal stability and both of the shape fixity ratio and shape recovery ratio could reach higher than 97% with the triggering temperature around 260 °C. Then controllable fabric composites with high temperature and reversible bidirectional shape memory effects were firstly constructed by incorporating of deliberately designed block copolyimide with commercialized polyimide fabric. The flexible fabric composites exhibited variable fixed shapes by regulating the thickness discrepancies between upper and lower layers, which showed good two-way shape memory properties with the shape recovery ratio of 98% during the programming process, providing a new sight of the exploration for high temperature shape-memory materials. Graphical abstract: A fabric composite with high temperature and reversible bidirectional shape memory effects was constructed by incorporating of deliberately designed block copolyimide with commercialized polyimide fabric. Image 1 Highlights: A series of block shape memory copolyimides with high T g were synthesized. The shape fixity ratio and recovery ratio of copolyimide could reach higher than 97%. Flexible fabric composites were fabricated by incorporating copolyimide with fabric. The composites showed bidirectional shape memory effects with high recovery ratios.